2002
DOI: 10.5194/smsps-3-79-2002
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new time scale for the Upper Miocene continental series of the Pannonian basin (Central Paratethys)

Abstract: Abstract. In this study we assert that most of the "Pontian" stratigraphic succession of western Hungary is much older than Pontian stage (older than 7 Ma). In fact, these strata form a clearly distinct chronostratigraphic unit between the Pontian strata (as they are defined in the type area of the Black Sea basin) and the Pannonian strata (as they are defined in the type area of the Vienna basin). To denote such a problematic chronostratigraphic interval we propose the introduction of a new stage (or substage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 18 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…Timing of this boundary is based on the age of the Szák Formation at 8.9 Ma (Cziczer et al 2009). Thus, our definition of the first Pannonian lacustrine depositional cycle upper boundary can also be correlated with the uppermost portion of the "Pannonian cycle PAN2" defined in the southernmost part of the DB by Sacchi & Horváth (2002).…”
Section: Late Miocene-pliocene Depositional Systems and Sedimentary Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Timing of this boundary is based on the age of the Szák Formation at 8.9 Ma (Cziczer et al 2009). Thus, our definition of the first Pannonian lacustrine depositional cycle upper boundary can also be correlated with the uppermost portion of the "Pannonian cycle PAN2" defined in the southernmost part of the DB by Sacchi & Horváth (2002).…”
Section: Late Miocene-pliocene Depositional Systems and Sedimentary Cmentioning
confidence: 99%
“…This is dated by folding of the Pannonian sediments -"Sava folds"; sensu Fodor et al (1999) and it first reached the northern regions during the Late Pliocene (indicated by the transpressive tectonic regime in the Western Carpathians causing their accelerated uplift; sensu Minár et al 2011). All these tectonic events were induced by the movement of the Adriatic plate northward (Sacchi & Horváth 2002;Ruszkiczay-Rüdiger et al 2005;Horváth et al 2006).…”
Section: Late Miocene and Pliocene Geodynamics And Development Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…commonly along deep and old structural weakness zones of the basement) that encountered a shallow subsurface zone of water-saturated filled sedimentary basins in the region [5]. The various thickness of the shallow marine and fluvio-lacustrine siliciclastic Neogene sedimentary infill [60][61][62][63][64][65] over the fractured, commonly karstic Mesozoic and Paleozoic carbonatic and metamorphic rock units [66][67][68], provided a combined aquifer that the rising mafic magma interacted with. As a result, the Pannonian Basin was a playground of phreatomagmatic volcanism through the Late Miocene to Pleistocene [58,69,70].…”
Section: Maars Related To Na-alkalic Rocksmentioning
confidence: 99%
“…In the Neogene, shortly before the volcanism started, a large lake, Lake Pannon, occupied the Pannonian Basin [46][47][48][49]. The lacustrine sandstones, mudstones and marls of the brackish Lake Pannon are the base of the immediate underlying pre-volcanic substrate of the BBHVF [48,[50][51][52][53][54]. Prior to the volcanism the BBHVF area was most likely an alluvial plain [38,48].…”
Section: Geological Setting and Formation Of Hegyestűmentioning
confidence: 99%